2018
DOI: 10.1002/app.46918
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the liquid oxygen compatibility of epoxy via the addition of surface‐modified boehmite

Abstract: To improve the liquid oxygen compatibility and cryogenic mechanical properties of epoxy resin, we synthesized and characterized a hybrid compound (functionalized boehmite) containing boehmite, phosphorus, and silicon element. The thermal properties and liquid oxygen compatibility of the composites were investigated in detail. The results show that the addition of functionalized boehmite increased the char residue obviously but had little effect on the thermal decomposition temperature and glass-transition temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…The functioned nanomaterial could improve the flame retardancy, thermal stability and cryogenic mechanical properties of the resin system. Mixing a certain amount of the DOPO modified nanofiller (boehmite) into pure epoxy could also improve the liquid oxygen compatibility of the resin system [157]. Peng et al synthesized a phosphorous-containing benzoxazine monomer (PBA), and treated PBA as harder to cure EP [158].…”
Section: Research Progress In Liquid Oxygen Compatibility Of Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The functioned nanomaterial could improve the flame retardancy, thermal stability and cryogenic mechanical properties of the resin system. Mixing a certain amount of the DOPO modified nanofiller (boehmite) into pure epoxy could also improve the liquid oxygen compatibility of the resin system [157]. Peng et al synthesized a phosphorous-containing benzoxazine monomer (PBA), and treated PBA as harder to cure EP [158].…”
Section: Research Progress In Liquid Oxygen Compatibility Of Polymersmentioning
confidence: 99%
“…Due to the flame-retardant ability of phosphorous and the thermal stability of benzoxazine [159,160], the modified polymer mentioned above showed great potential manufacturing the LOX composites tank for its comprehensive performance (mechanical properties and LOX compatibility). Therefore, it has been proven that improving the flame retardancy, thermal stability of polymer is an effective way to enhance its LOX compatibility [150][151][152][153][154][155][156][157][158].…”
Section: Research Progress In Liquid Oxygen Compatibility Of Polymersmentioning
confidence: 99%
“…When the KH550–MXene content was increased to 3%, one burning phenomenon occurred out of 20 experiments, indicating that the liquid-oxygen compatibility of EP nanocomposites decreased. 45 IRS was computed according to formula (1) below:…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 35 ] synthesized EP modified by 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (ODOPB) and EP-A, and the enhanced flame retardancy and thermal stability were proven to improve the LOC of EP, but the mechanism of ODOPB affecting the LOC has not been analyzed in depth. Wang et al [ 36 ] introduced a hyperbranched compound containing phosphorus, silicon elements and boehmite into EP; the results showed that the modified EP could achieve LOC, but the tensile properties of the modified EP at 90 K were decreased and the fracture toughness has not been studied. Li et al [ 27 ] utilized DOPO-PGE to modify EP, and the results indicated that DOPO-PGE was a promising additive in the field of enhancing the LOC of the EP matrix and CFRP, but the mechanical properties of DOPO-PGE-modified EP need further research.…”
Section: Introductionmentioning
confidence: 99%